Academic Literacies in a South African Writing Centre: Student Perspectives on Established Practices - Evans-Tokaryk, Tyler; Shabanza , Kabinga Jack (Discourse and Writing/Rédactologie, 2022)
Through a case study conducted in 2014 and 2015 at the University of X in South Africa, the researchers collected focus group and survey data to develop a better understanding of the kinds of students who use the university’s Writing Centre and their perceptions of the support they receive. The research question at the core of their study asks whether a South African writing centre’s academic literacies practices and philosophy should be adapted or changed to better serve today’s students. The results of the study demonstrate that the vast majority of students who visit the writing centre speak English as an additional language and believe they need more writing support with a focus on lower order concerns than that currently offered through the academic literacies approach at the university. The researchers concluded that the South African undergraduate students at the University of X need differentiated forms of writing support that go beyond the orthodoxies of the current academic literacies approach embraced by the University’s writing centres. The researchers urge writing centres to acknowledge the need to develop interventions and models of support that target English as an Additional Language (EAL) students without adopting a deficit-perspective and without abandoning the long-term project of challenging the privileged status of the English language within the institution.